Metabolic and performance effects of warm-up intensity on sprint cycling - Wittekind, A.; Beneke, R. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Warm-up is generally considered beneficial for performance, although the reduction in anaerobic glycolytic metabolism may be detrimental to sprinting. This study examined the effect of warm-up intensity on metabolism and performance in sprint cycling. The mean power was determined during a 1-min sprint on 11 trained males preceded by easy (WE), moderate (WM) or hard (WH) warm-up and a 10-min recovery. Aerobic, anaerobic glycolytic and phosphocreatine energy provision to the sprint was determined from oxygen uptake and lactate production. Blood lactate concentration before the sprint increased with the warm-up intensity (WE: 1.2+/-0.3; WM: 2.0+/- 0.3; WH: 4.2 +/- 0.9mmol/L, P<0.001), withWH reducing the increase in lactate production during exercise vs WE (WE: 11.6+/-1.6; WM: 10.9+/- 1.9; WH: 9.2+/- 1.4 mmol/L, P<0.05). Despite the lower relative anaerobic glycolytic energy provision in WH vs WE (WH: 38+/- 5; WM: 36+/- 6; WE: 34+/- 3%, P<0.05), the mean power was unaffected (WE: 516+/-28; WM: 521+/-26; WH: 526+/-34W, P>0.05) due to increased oxygen uptake in WH during the sprint (WE: 3.2+/- 0.4; WM: 3.3+/-0.3; WH: 3.4+/-0.4 liters, P<0.05). This study supports a warm-up-induced reduction in glycolytic rate, although sprint performance, at least of a long duration, may be maintained due to increased oxygen utilization. Abstract from author